Examining the Role of School Climate in Promoting Cross-Cultural Emotional Wellness and Psychological Resilience Among Students in Army Schools - Dhandapani, Sudha; Kaur, Kamaljeet (Journal of Interdisciplinary Studies in Education, 2026)
This study investigates the influence of school climate on the emotional wellness and psychological resilience of students in army schools, which offers cross-cultural dynamics. The unique environment has students from diverse regional and cultural backgrounds due to the mobility of military families. The research explores how supportive leadership, peer relationships, inclusivity, and emotional safety contribute to students’ emotional well-being and ability to adapt in challenging situations. The study utilizes Likert scale instrument to capture data from 120 students in secondary classes from 15 Army Schools across the Northeastern states of India. The findings aim to provide insight into the mechanisms through which school climate can foster emotional balance and resilience, guiding future policies for military-based educational institutions.